Reproducibility of Heart Rate Variability Indices at Post-maximal Exercise - Araújo, Jaqueline Alves; Peçanha, Tiago; Novelli, Fabiula Isoton; Mello, César Siqueira Aleixes; Moreira-Gonçalves, Daniel; Arsa, Gisela; Cambri, Lucieli Teresa (International Journal of Sports Medicine, 2020)
To analyze whether heart rate variability is reproducible after maximal exercise, 11 men (22.1±3.2 years) performed four incremental exercise tests followed by passive or active recovery. There was high reliability (intraclass coefficient correlation: 0.72–0.96) and fair-to-excellent agreement (coefficient of variation: 7.81–22.09%) in passive recovery, as well as moderate-to-high reliability (intraclass coefficient correlation: 0.50–0.87) and good agreement (coefficient of variation: 11.08–20.89%) in active recovery for LnRMSSD index. There was moderate-to-high reliability (intraclass coefficient correlation: 0.51–0.81) and good agreement (coefficient of variation: 10.41–18.87%) in most of the analyzed time points, in both recovery types for LnSDNN. In both types of recovery, the time domain heart rate variability 5–10 min indices (passive: intraclass coefficient correlation : 0.87–0.88; coefficient of variation: 7.67–13.44%; active: intraclass coefficient correlation 0.59–0.80; coefficient of variation: 14.62–16.26%) presented higher intraclass coefficient correlation and lower coefficient of variation than the spectral heart rate variability indices (passive: intraclass coefficient correlation: 0.71–0.87; coefficient of variation: 12.33–34.21%; active: intraclass coefficient correlation: 0.46–0.77; coefficient of variation: 24.41–105.12%). The LnRMSSD and LnSDNN indices analyzed in 30 s segments and the heart rate variability 5–10 min indices after maximal exercise in untrained healthy men showed satisfactory reproducibility, regardless of the type of recovery, with the time-domain indices showing higher reproducibility than the frequency-domain indices.
Keywords: reliability; agreement; autonomic nervous system; cardiac autonomic modulation; vagal reactivation; passive recovery